A nanoscale "yarn ball"-like heteropoly blue catalyst for extremely efficient elimination of antibiotics and dyes. (1st September 2019) - Hu, Yi; Li, Yulian; He, Junyong; Zhang, Kaisheng; Liu, Tao; Huang, Xingjiu; Kong, Lingtao; Liu, Jinhuai
Abstract: Fenton system is one of the most popular methods to eliminate antibiotics and dyes in aquatic environment. However, the existed Fenton system is limited by various factors such as potential second pollution and narrow pH range. In this study, we report that the bottlenecks for high strength antibiotics and dyes wastewater treatment at a wide pH range can be well tackled by the nanoscale "yarn ball"-like Mo/W-containing heteropoly blue (HPB) catalyst Mg2 Ti6 Mo23 O119 SiW12 (1 ). This novel catalyst displayed extremely efficient elimination for several typical organic contaminants such as malachite green (MG), tetracycline (TC) and methyl orange (MO). Compared with other materials reported in previous papers, the catalytic performance of 1 in degradation of the organic contaminants of high concentrations increased several times. More than 90% of antibiotics and dyes are degraded within 60 min. Electron spin resonance (ESR) experiments and UV–vis spectra confirmed that the catalytic mechanisms of 1 could mainly ascribe to the 1 /H2 O2 process and the possible photocatalytic oxidation of adsorbed H2 O by holes (h + ) in the valence band (VB) of 1 surface generated · OH for extremely efficient degradation of organic contaminants. This work widens the optimal pH values up to neutral condition and it's significant for the expansion of the heterogeneous Fenton-like catalyst family and its application in the field of water treatment. Graphical abstract: Image 1 Highlights: A HPB Fenton-like catalyst for degradation of antibiotics and dyes. More than 90% of antibiotics and dyes are degraded within 60 min. Widening the optimal pH values up to neutral condition. Expanding the Fenton-like catalyst family and its application in the field of water treatment.